1993
DOI: 10.1002/mrm.1910300107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of macromolecule resonances in the 1H NMR spectrum of rat brain

Abstract: The 1H NMR spectrum of the macromolecule fraction of rat brain cytosol was investigated following centrifugation and dialysis to remove low molecular weight metabolites and peptides (< 3500 daltons). At least seven well resolved resonances were detected between 0.9 and 3.0 ppm in the 1H NMR spectrum of rat brain cytosol after dialysis, several of which cannot be observed in vivo due to overlap with N-acetylaspartate, glutamate, glutamine, creatine, and gamma-aminobutyric acid. Several cross-peaks detected in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
225
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(237 citation statements)
references
References 20 publications
11
225
1
Order By: Relevance
“…The apparent structure of the spline baseline suggested the presence of biological signals underlying the narrow metabolite peaks, consistent with previous reports of large molecular weight compounds contributing to the spectrum of brain extracts (14) with relatively short T 1 and T 2 compared with acid-extracted metabolites. We therefore further assessed potential macromolecule contributions to the in vivo spectrum and the effect on the quantification of including a measured macromolecule spectrum to the LCModel approach.…”
Section: Figsupporting
confidence: 89%
See 1 more Smart Citation
“…The apparent structure of the spline baseline suggested the presence of biological signals underlying the narrow metabolite peaks, consistent with previous reports of large molecular weight compounds contributing to the spectrum of brain extracts (14) with relatively short T 1 and T 2 compared with acid-extracted metabolites. We therefore further assessed potential macromolecule contributions to the in vivo spectrum and the effect on the quantification of including a measured macromolecule spectrum to the LCModel approach.…”
Section: Figsupporting
confidence: 89%
“…The spectra acquired with TE ϭ 2 ms and TE ϭ 20 ms using this t IR null ( Fig. 3) represent mostly macromolecule signals which have been reported with short T 1 (14). Major resonances were observed at 0.916 ppm (labeled M1, which was used as reference), 1.21 (M2), 1.39 (M3), 1.67 (M4), 2.04 (M5), 2.26 (M6), and 2.99 ppm (M7).…”
Section: Baseline In 1 H Spectramentioning
confidence: 79%
“…Spectra measured at short echo-times are further complicated by broad signals ascribed mainly to cytosolic proteins [10]. At high magnetic fields the largely field-independent linewidth of the signals of macromolecules increasingly approaches that of metabolites and an experimental assessment of macromolecular contribution to the proton spectrum may become crucial for accurate metabolite quantification.…”
Section: Introductionmentioning
confidence: 99%
“…H-NMR spectroscopy can provide unique and important structural information about plasma membrane composition and function in cells and tissues with the additional advantage of being nondestructive to the system under study (9)(10)(11)(12). Correlation spectroscopy (COSY) 1 experiments, a standard method for establishing proton coupling networks, have been used to detect and identify amino acids, phospholipids, plasma membrane triglycerides and cell surface carbohydrates in cancer cells and tissues (13)(14)(15). From these studies, NMR measurable changes in triglycerides and carbohydrates were found to correlate with cancer cell tumorigenesis and metastatic potential.…”
Section: Introductionmentioning
confidence: 99%